Opportunistic records of jungle cat (Felis chaus) and their activity pattern in Koshi Tappu Wildlife Reserve, Nepal - Mishra, Rama; Gautam, Birendra; Shah, Shyam Kumar; Subedi, Naresh; Pokheral, Chiranjibi Prasad; Lamichhane, Babu Ram (Nepalese Journal of Zoology, 2020)
Jungle cat (Felis chaus) is one of the widely distributed but less studied species in Nepal. We studied jungle cat distribution and their activity pattern in Koshi Tappu Wildlife Reserve (KTWR), Nepal. Photographs of the jungle cats obtained during camera trapping survey targeted to fishing cats in the winter season of two consecutive years (2016 and 2017) were used for this study. With an effort of 525 trap days from 69 stations, we obtained a total of 234 images/videos of jungle cats on 37 occasions from 15 stations. We recorded jungle cats distributed in the eastern buffer zone of the KTWR. All the jungle cat photographs were obtained in the night with peak activity within a couple of hours following the sunset. We suggest to carry out focused study specific to jungle cats to understand their distribution, status and diet.